Computational Prediction of Antimalarial Potential of Eurycoma longifolia Phytochemicals Targeting Plasmodium falciparum - Awisarita, Wiwara; Farid, Muhammad (Faculty of Medicine, Universitas Jember, 2025)
Falciparum malaria, caused by Plasmodium falciparum, remains a major global health threat, complicated by the emergence of drug-resistant strains that undermine the efficacy of current artemisinin-based therapies. Eurycoma longifolia Jack (Pasak Bumi), a medicinal plant native to Southeast Asia, has long been used in traditional medicine for treating malaria and infectious diseases. With increasing resistance of Plasmodium falciparum to conventional drugs, the search for novel antimalarial agents is crucial. This study aimed to predicted the antimalarial potential of bioactive compounds from E. longifolia through a computational approach targeting Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH). Ten phytochemicals were selected and their 3D structures were prepared using PyRx and Open Babel. Molecular docking simulations were conducted using AutoDock Vina, with artemisinin as a control. Docking validation achieved an RMSD of 0.823 Å, confirming protocol reliability. Among the tested ligands, syringic acid showed the highest binding affinity -6.7 kcal/mol, followed by scopoletin -6.6, and fraxidin -6.4, with key interactions involving residues His185, Val532, and Phe188. Toxicological predictions indicated variability, with 1,1′-biphenyl-3,3′-dicarboxylic acid exhibiting the highest acute toxicity. Despite no compound surpassing the native ligand's binding energy -7.9 kcal/mol, several exhibited promising interactions and favorable safety profiles. This study highlights E. longifolia as a promising source of phytochemicals for antimalarial drug discovery. Further experimental studies and molecular dynamics simulations are recommended to validate these findings and optimize compound efficacy.